Survey of knowledge of outpatients on locations in the refrigerator for eye drop keeping. - Pornvichitpisan , S.; Laohapojanart , N. (Chulalongkorn Medical Journal, 2023)
Rational : Some kinds of eye drop such as Latanoprost, Chloramphenicol, Cefazolin, Ceftazidime, Vancomycin and Amphotericin B need to be kept at the temperature of 2-8 OC to maintain their efficiency. Patients are usually recommended to keep these drugs in the refrigerator while dispensing. However, the temperature in the refrigerator is not consistent especially the refrigerator’s door has higher temperature than other parts. Objective : To survey the knowledge of patients regarding the location in the refrigerator that usually keeps the eye drop after receiving from the pharmacists Method Design : The research was designed as description study Method and Sample : The subjects were the patients who showed up at the Pharmacy Unit of the Outpatient Department of King Chulalongkorn Memorial Hospital, where patients with eye diseases receive the medicine. The data were prospectively collected by questioner who interviewed the outpatients in February 2009. Inclusion criteria were: patients who were prescribed eye drop by doctors, and the medication should be kept in the refrigerators such as Latanoprost, Chloramphenicol, Cefazolin, Ceftazidime, Vancomycin and Amphotericin B Result : In all 300 patients were recruited into the study 279 (93%), 21 (7%) know and do not know that they should keep their eye drop in the refrigerators respectively. The patient got the knowledge of keeping eye drop in the refrigerators from various sources, namely: doctors 227 (75.6%), pharmacists 11 (3.7%), nurses 2 (0.7%), stickers 39 (13%) and others 21 (7%). Those who received the information from doctors and pharmacists kept the eye drop in the appropriate location (2-8 OC) about 33 (11%) and 6 (2%). About the positions in refrigerators find that patients keeping in the middle of refrigerators 39 (13%), under freezing compartment 18 (6%), at the door of refrigerators 192 (64%) and salad drawer 33 (11%) Conclusion : Most patients know that keeping eye drop in the refrigerators can maintain the efficiency of the eye drop after receiving data from doctors. However, few patients keep their eye drop in the appropriate position. Therefore, pharmacists should give information about the optimal temperature in refrigerators to maintain the potency of medicine through shelf life.